PENGEMBANGAN MEDIA PERMAINAN KARTU DOMICHEM PADA MATERI TERMOKIMIA DENGAN PENDEKATAN KONSTRUKTIVIS UNTUK MELATIHKAN KETERAMPILAN BERFIKIR KRITIS - Rusly Hidayah; Esa Nur Isma (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2018)
A research has been conducted to develop a game media Domichem to improve critical thinking skills of students on Thermochemistry material. Domichem is adobted game of dominoes. The diffetenties located on the side of the domino being replaced with keywords on thermochemical material. Research conducted at SMA Al-Hikam Bangkalan Madura. Limited trial using a sample of 12 students. Preliminary data before treatment given 0 out of 12 students completed the pretest. After getting treatment 10 students completed the posttest. Thus obtained by classical successness 83.33%.